2009
DOI: 10.1074/jbc.m109.002725
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Protein Masks the DNA Binding Interface of Forkhead Transcription Factor FOXO4

Abstract: The role of 14-3-3 proteins in the regulation of FOXO forkhead transcription factors is at least 2-fold. First, the 14-3-3 binding inhibits the interaction between the FOXO and the target DNA. Second, the 14-3-3 proteins prevent nuclear reimport of FOXO factors by masking their nuclear localization signal. The exact mechanisms of these processes are still unclear, mainly due to the lack of structural data. In this work, we used fluorescence spectroscopy to investigate the mechanism of the 14-3-3 protein-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
5
49
1
Order By: Relevance
“…This could be attributed to a bound fraction of DANS-TRE sensing lower solvation and decreased microenvironmental polarity in the binding pocket of the complex. The value is consistent with values commonly found for the dansyl moiety covalently linked to globular proteins (34,35). The fractional intensity of the 14.3-ns component in the Bmh1:pNth1 1-751 (E674A) complex (4.2%) is significantly higher than in the presence of pNth1 1-751 (E674A) (0.5%) or Bmh1 alone (1.3%), where the presence of the long component likely indicates some nonspecific interaction of DANS-TRE with Bmh1.…”
Section: Resultssupporting
confidence: 78%
“…This could be attributed to a bound fraction of DANS-TRE sensing lower solvation and decreased microenvironmental polarity in the binding pocket of the complex. The value is consistent with values commonly found for the dansyl moiety covalently linked to globular proteins (34,35). The fractional intensity of the 14.3-ns component in the Bmh1:pNth1 1-751 (E674A) complex (4.2%) is significantly higher than in the presence of pNth1 1-751 (E674A) (0.5%) or Bmh1 alone (1.3%), where the presence of the long component likely indicates some nonspecific interaction of DANS-TRE with Bmh1.…”
Section: Resultssupporting
confidence: 78%
“…These proteins contain a nuclear localization sequence whose interaction with the nuclear import machinery is inhibited upon the 14-3-3 protein binding. Recently, we have also shown that the forkhead transcription factor FOXO4 is inhibited by a similar mechanism involving the physical occlusion of its DNA binding interface (26).…”
Section: Discussionmentioning
confidence: 99%
“…Labeling of 14-3-3 Protein Mutants by 5-Iodoacetamidofluorescein for FRET Measurement-Covalent modification of the 14-3-3 protein mutants containing a single cysteine residue with the thiol-reactive probe 5-iodoacetamidofluorescein was carried out as described elsewhere (26,28). Briefly, we constructed two mutants containing a single cysteine residue (either at position 25 or at position 189) of human monomeric 14-3-3 protein (mutant S58D) (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations